2016
DOI: 10.3889/oamjms.2016.026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of NBF Gingival Gel Application in the Treatment of the Erosive Lichen Planus: Case Report

Abstract: The therapy of erosive lichen planus (ELP) has been particular problem in the treatment of oral lesions. This case of ELP in male patient 29 years old was treated with topic application of the NBF gingival gel, three times a day after meal, previously rinsed with Clorhexidine gluconate 0.12%. After 5 days of treatment, initial improvements were recorded, and after two weeks of application of the NBF gingival gel we observed significant improvement. Clinical monitoring after the fifth day showed mild epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, it also contains eucalyptus globulus oil that has been shown to have antibacterial effects against a variety of bacteria [ 35 ]. This gel also contains vitamin C and E, both accelerating gingival wound healing and preventing gingival bleeding in preclinical in vivo studies [ 23 , 36 ]. But the present in vitro study has not been able to demonstrate any regenerative properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it also contains eucalyptus globulus oil that has been shown to have antibacterial effects against a variety of bacteria [ 35 ]. This gel also contains vitamin C and E, both accelerating gingival wound healing and preventing gingival bleeding in preclinical in vivo studies [ 23 , 36 ]. But the present in vitro study has not been able to demonstrate any regenerative properties.…”
Section: Discussionmentioning
confidence: 99%
“…Besides antibacterial agents, periodontal gels nowadays also include regeneration factors such as: (1) aloe vera that is a well-known plant with positive effects on wound healing and regeneration [ 17 ]; (2) chitosan that is a biocompatible marine polysaccharide polymer used in several biomedical applications, including wound healing [ 18 ]; (3) hyaluronic acid (HA) that is a naturally occurring linear polysaccharide of the extracellular matrix (ECM) of connective tissues that has been shown to promote tissue regeneration [ 19 ]; (4) asiaticoside that is a component extracted from the Centella asiatica plant and commonly used as a treatment for wounds and burns [ 20 ]; (5) chondoitrin sulfate that is one of the main glycosaminoglycans that compose the ECM and favors wound closure [ 21 ]; (6) amelogenin fraction of porcine enamel matrix (Emdogain ® or EMD) that stimulate cell-matrix interactions and promote the regeneration of damaged periodontal tissue [ 22 ] and (7) antioxidants like vitamin C and E that control oxidative stress in wound healing and play important roles in the acceleration of healing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Popovska et al . ( 24 ) published a case report of a patient that obtained the complete healing of oral lesions of erosive lichen planus by applying TG gel 3 times a day for 4 weeks. Additionally, in a randomized controlled study, Dednath et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has shown that propolis may have beneficial effects in patients, since propolis extracts significantly reduce serum TNF-α and CRP concentrations [ 30 ] and have an inhibitory effect in MMP-9 activity [ 31 , 32 ]. Recently, a formulation as a gingival bioadhesive gel-containing propolis extract, nanovitamin C, and nanovitamin E has demonstrated clinical improvements when treating peri-implant mucositis [ 33 ], in the pain reduction after the surgical extraction of impacted lower third molars [ 34 ], and in the treatment of oral erosive lesions of OLP [ 35 ]. It was, therefore, the objective of this randomized clinical trial to evaluate the efficacy and safety of the use of this bioadhesive gel-containing propolis extract, nanovitamin C, and E as an adjuvant to professional plaque removal in the treatment of DG.…”
Section: Introductionmentioning
confidence: 99%